Story of the Scottish Parliament : the first two decades explained. (Edinburgh University Press, 2019)
Marking the first twenty years of the Scottish Parliament, this collection of essays assesses its impact on Scotland, the UK and Europe and compares progress against pre-devolution hopes and expectations. It brings together the voices of ministers and advisers, leading political scientists and historians, commentators, journalists and former civil servants – building an authoritative account of what the Scottish Parliament has made of devolution. The Story of the Scottish Parliament is an essential guide to the powers Holyrood may need for Scotland to flourish in an increasingly uncertain world.